Automatic generation of android SQLite database components - Musleh, Iman; Zain, Samer; Nawahdah, Mamoun I.; Salleh, Norsaremah (IOS Press, 2018)
Mobile applications (apps) are becoming ubiquitous and at the same time getting more complex to develop. Specific development tools and techniques are always essential to facilitate the development of reliable and cost effective mobile apps. However, a large fraction of Android app developers are known to be novice and come from non-computing background. To assist developers, this paper addresses the problem of automatic generation of Android database components, and presents a technique for creating SQLite database and APIs. The technique is based on a tool named Android SQLite Creator (ASQLC) that can automatically generate Android SQLite database as well as the API classes that perform read/write operation on that database. To evaluate the tool, a preliminary experiment was conducted by junior computer science students in building a small size Android database. This preliminary evaluation shows that our tool can be usable and promising particularly for novice developers.